A knowledge, attitude and practices (KAP) study on prevention through design: a dynamic insight into civil and structural engineers in Malaysia. (3rd March 2020) - Che Ibrahim, Che Khairil Izam; Belayutham, Sheila
ABSTRACT: The concept of Prevention through Design (PtD) has received increasing attention in various countries, as part of the effort to enhance the safety of construction works. In Malaysia, the Occupational Safety and Health in Construction Industry (Management) (OSHCI(M)) guideline, which is based on the PtD concept, was introduced in 2017 to transform the safety practices in the construction industry. Due to the recent introduction to OSHCI(M), this study aims to explore the PtD knowledge, attitude and practices (KAP) among Civil & Structural (C&S) engineers towards OSHCI(M) implementation. Data were collected from 49 C&S engineers in Malaysia using a KAP questionnaire and discussion forum based on three series of workshops. Results from the forum sessions were then collated into a framework and illustrated using a dynamic approach called Causal Loop Diagram (CLD). The findings revealed that the current state of C&S engineers' knowledge still requires improvement, particularly on the PtD principles. The practices of PtD were mostly work-in-progress, but the majority of them have been very supportive on the implementation of PtD. Three recommendations for improving the PtD implementation were proposed: the external forces, industry dynamics and operational organisation factors. The relationship demonstrated in the CLD shows that the reliance on external forces will be reduced with the increase in industry dynamics that coherently enhances also the operational organisation towards PtD. This study extends the PtD literature in construction context as well as provides the status quo on the appreciation of PtD in the local context towards total implementation of OSHCI(M).